Mainstreaming Women Farmers to Agricultural Extension Services in India: Perception of Extension Personnel - Sah, Uma; Dubey, Shantanu Kumar; Singh , S. K.; Kumar , Rajesh; Singh, Deepak; Krishna, Radha (Indian Journal of Extension Education, 2015)
The poor access of women farmers' to agriculture extension services is an issue of concern with respect to the efficacy of  the agriculture production situation in India. The present favorable policy environment enabling women farmers in  accessing the extension services, the extension personnel plays the crucial role of translating these policies in achieving  the desired results. In an attempt to comprehend empirically the extension personnel's perception of the issue relating to  mainstreaming women farmers to agricultural extension services in India, the study was conducted among 150 Extension  Personnel (EP) who participated in capacity enhancement programmes during 2008-13 at ICAR- Indian Institute of  Pulses Research (IIPR), Kanpur. Research variables included perception of EP on women farmers' contribution to  farming related activities, engagement of female workforce in respective district extension system, the issues related to  involving women farmer in agricultural extension activities and the potential interventions to overcome the perceived  issue. Finding revealed that in overall pooled data more than half (56%) of EP observed that woman farmers contributed  21-40 per cent to the overall agricultural activities, while 23 per cent of them perceived that women farmers contributed  41-60 per cent of the total labour to agriculture activities in their respective districts. In depth activity analysis showed  that majority of the respondents reported that activities like weeding (87%), harvesting (85%), seed sowing (69%) and  threshing (48.6%) were performed by women farmers. Regarding the strength of female extension staff in their districts,  about 51 per cent of the EP revealed that the percentage of women extension staff was 0 to 5 per cent of the total existing  staff strength. Majority of the EP also perceived that social taboos prevented women's involvement in the extension  activities (61%) besides their illiteracy (39 %). Nearly half (48 %) of EPwere not satisfied with the present level of women  farmers' access to agriculture extension services and about 83.3 per cent opined that women farmers need to be adequately  involved in the agriculture extension activities. About 61 percent of them viewed that for better reach of extension  services to women farmers, appointment of women extension staff needs priority attention. For mainstreaming women  farmers in agricultural extension activities in India, majority of the EP suggested that designing specialized need based  trainings for women farmers (50 %), approaching women in groups through SHGs or women's club (20 %) and reserving  thirty per cent seats for women extension staff (15%) in the department may ensure better access of agricultural extension  services to women farmers in India.
Keywords: Agricultural extension services; mainstreaming women farmers